Vaccination Coverage of Infants and Young Children in a Selected Rural area of Mymensingh (Community Based Medical Journal, 2021)
This study was conducted to estimate vaccination coverage of infant and young children in a selected rural area of Mymensingh. This was done on the background that vaccine preventable diseases are major causes of under-5 mortality and morbidity in Bangladesh. Though EPI coverage in Bangladesh is high still there are reported cases of meningitis, pneumonia and measles. This was a community-based cross-sectional descriptive study conducted among 240 children belonging from birth to 24 months age group from Churkhai village of Bhavokhali union, Sadar Mymensingh during January 2019 as a part of Residential Field Site Training of 3rd year students under the guidance of Department of Community Medicine of Community Based Medical College Bangladesh. The sampling technique was purposive. A pre-designed, pre-tested questionnaire has been used to collect required information by face to face interviewing mothers of infant and young child with verification of immunization card. Out of total children between birth to 24 months age group surveyed, 121 (50.42%) were males and 119 (49.58%) were females. Most of them 217 (90.42%) were fully immunized and 23 (9.58%) were partially immunized. BCG vaccination was 100% though 19 (7.92%) were 2 months late. Pentavalent, PCV, b OPV, f IPV vaccination coverage was 92.89% each, though 5 (2.37%) were 2 months late. Measles-Rubella coverage was 83.04%. Vaccination coverage was better than the finding of other studies in Bangladesh and neighboring countries except Measles-Rubella coverage. We should motivate mothers to attain a full vaccination coverage of 100%.CBMJ 2020 January: Vol. 09 No. 01 P: 19-24